Assessing the need for a doctor of philosophy (Ph.D.) degree in Endodontics: perspective and implication for advancing dental education and research in Saudi Arabia - Loai Alsofi (BMC Medical Education)
Abstract Aim This study aims to evaluate the necessity and feasibility of integrating a Doctor of Philosophy (Ph.D.) degree into Endodontic programs at the Faculty of Dentistry King Abdulaziz University, (KAUFD), Jeddah, Saudi Arabia, and to gather insights from key stakeholders regarding the value and necessity of a Ph.D. in enhancing the field of Endodontics. Materials and Methods An online questionnaire link was distributed among potential Ph.D. candidates and key decision-makers in Endodontics in Saudi Arabia through social media and emails to members of the Saudi Endodontic Society and the Saudi Endodontic Journal. The questionnaire assessed demographics, professional background, interest in Ph.D. programs, program preferences, perceived need for Ph.D. programs in various sectors, and university selection criteria. Data were analyzed using IBM SPSS Statistics (Version 23). Results 141 responses were received. Most respondents were aged 31–40, with an almost equal gender distribution. In terms of current position, a significant number were Endodontic consultants (35.7%) and Endodontic residents/Master students (28.6%) (P = 0.006). Additionally, a considerable proportion of probable prospective students had less than 5 years of expertise (45.7%) (p = 0.013), and the highest degree held by many was a bachelor’s degree (35.7%) (P = 0.007). Key considerations for prospective students were program duration, Saudi Commission for Health Specialists (SCFHS) recognition, part-time options, and cost. The importance of acquiring research skills, such as learning new research technologies and gaining publication experience, was also highlighted. Conclusion The findings strongly suggest a need for a Ph.D. program in Endodontics in Saudi Arabia. The results provide valuable insights for developing a program that aligns with potential candidates’ and key stakeholders’ needs and preferences, thereby advancing Endodontic research and education within the country.